The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5194/hess-17-565-2013
|View full text |Cite
|
Sign up to set email alerts
|

An ensemble approach to assess hydrological models' contribution to uncertainties in the analysis of climate change impact on water resources

Abstract: Abstract. Over the recent years, several research efforts investigated the impact of climate change on water resources for different regions of the world. The projection of future river flows is affected by different sources of uncertainty in the hydro-climatic modelling chain. One of the aims of the QBic 3 project (Québec-Bavarian International Collaboration on Climate Change) is to assess the contribution to uncertainty of hydrological models by using an ensemble of hydrological models presenting a diversity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
92
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 50 publications
9
92
0
Order By: Relevance
“…They concluded that model structures and parameter identification are important sources of uncertainty under a changing climate. Velázquez et al (2013) confirmed that the selection of a hydrological model affects climate change impacts conclusions, especially for low flows on two dissimilar catchments, in Germany and Canada.…”
Section: G Seiller and F Anctil: Climate Change Impacts On The Hydrsupporting
confidence: 59%
See 1 more Smart Citation
“…They concluded that model structures and parameter identification are important sources of uncertainty under a changing climate. Velázquez et al (2013) confirmed that the selection of a hydrological model affects climate change impacts conclusions, especially for low flows on two dissimilar catchments, in Germany and Canada.…”
Section: G Seiller and F Anctil: Climate Change Impacts On The Hydrsupporting
confidence: 59%
“…Vicuna et al, 2007;Minville et al, 2008;Kay et al, 2009;Boyer et al, 2010;Görgen et al, 2010;Teng et al, 2012;Jung et al, 2012) while others focused on specific ones (e.g. Ludwig et al, 2009;Gardner, 2009;Poulin et al, 2011;Bae et al, 2011;Teng et al, 2012;Velázquez et al, 2013). However, all these works are based on ensemble intercomparison and advocate the necessity of assessing uncertainties before, for example, comparing river discharges over reference (REF) and future (FUT) periods.…”
Section: Introductionmentioning
confidence: 99%
“…A common finding is that hydrological model uncertainty is less important than other uncertainty sources (i.e. GCM), but cannot be ignored (Prudhomme and Davies, 2009;Teng et al, 2012;Thompson et al, 2013;Velázquez et al, 2013). However, for certain hydrological indicators (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In regard of the climate models, also the choice of GCM and RCM can have a large impact on the results and generally an ensemble of projectionsencompassing different GCMs, RCMs and emission scenarios -is recommended in hydrological climate change impact assessment (Hewitt and Griggs 2004;Collins 2007). A clear distinction on the relative effects of hydrological model (HM) uncertainty and climate model (CM) uncertainty to the projected discharge uncertainty has not been concluded; results vary between studies depending on catchment climate and hydrological variable studied (Hagemann et al 2013;Velázquez et al 2013;Vetter et al 2015). However, the impact of HM structural uncertainty on projected discharge changes can be significant due to, for instance, the differences in the representation of evapotranspiration and snow/ice accumulation/melting processes (Poulin et al 2011;Viviroli et al 2011).…”
Section: Introductionmentioning
confidence: 99%